Positive electrode active material for lithium ion secondary battery, lithium ion secondary battery, and method for producing positive electrode active material for lithium ion secondary battery

The lithium transition metal oxide cathode material with specific composition and surface modifications addresses the limited discharge capacity of existing lithium-ion batteries, achieving higher energy efficiency and stability by optimizing the distribution of Ni, Mn, and Zr within the battery structure.

CN119725514APending Publication Date: 2025-03-28HONDA MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411049007.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-08-01
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Current lithium-ion batteries, particularly those using LiNi0.5Mn0.5O2 as the cathode material, have limited discharge capacity between 4.35 and 2.75V, which hinders energy efficiency in applications like electric vehicles and hybrid electric vehicles.

Method used

Development of a lithium transition metal oxide cathode material with a specific chemical composition (Li1mNixMnyZrzO2) and surface modifications, including a higher Mn/Ni ratio and Zr incorporation, to enhance discharge capacity and energy efficiency, achieved through thermal processing and subsequent annealing to ensure uniform distribution of Ni, Mn, and Zr, thereby improving the material's structural stability and electrochemical properties.

Benefits of technology

The modified cathode material significantly increases discharge capacity, reduces the number of batteries required, lowers costs, and enhances cycle stability, leading to improved energy efficiency and longer battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725514A_ABST
    Figure CN119725514A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a positive electrode active material for lithium ion secondary batteries, with which it is possible to obtain a lithium ion secondary battery capable of further improving the discharge capacity; a lithium ion secondary battery using the positive electrode active material; and a method for producing the positive electrode active material for lithium ion secondary batteries. A positive electrode active material for a lithium ion secondary battery, the positive electrode active material having a lithium transition metal composite oxide as a main component, the lithium transition metal composite oxide being in the form of particles having an outer layer on the surface, the lithium transition metal composite oxide being represented by formula (1): LimNixMnyZrzO2 (in formula (1), m is in the range of 1.0 < = m < = 1.04, x is in the range of 0.47 < x < 0.58, y is in the range of 0.40 < = y < 0.50, and x is in the range of 0.20 < = y < 0.50). And z is in the range of 0 < z < 0.02, and the Mn / Ni ratio, which is the ratio of the number of Mn atoms to the number of Ni atoms in the outer layer, is 1.0-2.5 inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a lithium ion secondary battery, and a method for producing the positive electrode active material for a lithium ion secondary battery. Background Art

[0002] In recent years, research and development on secondary batteries that contribute to energy efficiency has been conducted. In particular, lithium-ion secondary batteries are becoming increasingly important as a power source for electric vehicles (EVs), hybrid electric vehicles (HEVs), and the like.

[0003] Positive electrode active materials have attracted attention as important components that determine the capacity of lithium-ion secondary batteries, and their development is being promoted. As positive electrode active materials used in lithium-ion secondary batteries, for example, composite oxides formed by replacing a portion of nickel and manganese in lithium nickel-manganese composite oxides with zirconium (Zr) have been reported (e.g., Non-Patent Document 1 and Patent Document 1). Prior art literature Non-patent literature

[0004] Non-patent literature 1: Yao, et al., “Facile synthesis of Li 2 ZrO 3 -modifiedLiNi 0.5 Mn 0.5 O 2 cathode material from a mechanical milling route for lithium-ionbatteries”Journal of Electroceramics.43,84-91(2019) Patent Literature

[0005] Patent Document 1: International Publication No. 2020 / 209239 Pamphlet Summary of the invention Problems to be solved by the invention

[0006] In Non-Patent Document 1 and Patent Document 1, the discharge capacity at 4.35 to 2.75 V is approximately 150 to 170 mAh / g, which leaves room for improvement.

[0007] The present invention is completed in order to solve the above-mentioned problems, and its purpose is to obtain a positive electrode active material for a lithium ion secondary battery that can further improve the discharge capacity of a lithium ion secondary battery, a lithium ion secondary battery using the positive electrode active material, and a method for manufacturing the positive electrode active material for a lithium ion secondary battery. Moreover, it further contributes to the efficiency of energy. Technical solutions to solve problems

[0008] In order to achieve the above object, the present invention provides the following technical solutions. [1] A positive electrode active material for a lithium ion secondary battery, comprising a lithium transition metal composite oxide as a main component, wherein: The lithium transition metal composite oxide is in the form of particles having an outer layer on the surface. The lithium transition metal composite oxide is represented by the following formula (1): Li m Ni x Mn y Zr z O 2 (1) (In formula (1), m is in the range of 1.0≤m≤1.04, x is in the range of 0.47<x<0.58, y is in the range of 0.40≤y<0.50, and z is in the range of 0<z<0.02) The ratio of the number of Mn atoms to the number of Ni atoms in the outer layer (Mn / Ni ratio) is 1.0 or more and 2.5 or less.

[0009] [1] The surface of the positive electrode active material for lithium ion secondary battery involved becomes manganese-rich. Therefore, even if the Ni content is reduced, the discharge capacity can be further increased. Therefore, in the lithium ion secondary battery using the positive electrode active material, the number of required batteries can be reduced, which helps to reduce costs. That is, it can contribute to the efficiency of energy.

[0010] [2] The positive electrode active material for a lithium ion secondary battery according to [1], wherein the ratio of the number of Ni atoms to the number of Zr atoms in the outer layer (Ni / Zr ratio) is 6.50 or more and 17.5 or less.

[0011] [2] The surface of the positive electrode active material for lithium ion secondary battery involved becomes rich in zirconium (Zr). Therefore, the increase of Ni valence and the decrease of Mn valence can be suppressed, and the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. Therefore, it can contribute to further energy efficiency.

[0012] [3] The positive electrode active material for lithium ion secondary batteries according to [1] or [2], wherein the positive electrode active material is 6 The spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR has a peak in the range of 500 to 800 ppm.

[0013] [3] The positive electrode active material for lithium ion secondary batteries has a peak in the range of 500 to 800 ppm. This means that the Li-O 6 Ni and Mn in adjacent transition metal layers are uniformly dissolved in solid solution, thereby contributing to further improvement of energy efficiency.

[0014] [4] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [3], wherein the positive electrode active material has a solid lithium ion secondary battery surface area of ​​100 nm and a surface area of ​​100 nm. 6 In the spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR), there is no peak in the range of 1475 to 1550 ppm.

[0015] [4] The positive electrode active material for lithium ion secondary batteries does not have a peak in the range of 1475 to 1550 ppm. This means that there is no peak due to Li 2 MnO 3 The peaks caused by this phenomenon show that there is no LiMn in the transition metal layer. 6 Therefore, it can contribute to further energy efficiency.

[0016] [5] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [4], which has no peak in the range of 42°≤2θ≤43° in an X-ray diffraction pattern using a Cu ray source.

[0017] [5] The positive electrode active material for lithium ion secondary batteries does not have a peak in the range of 42°≤2θ≤43°. This means that there is no peak due to Li 2 ZrO 3 The peak caused by the Zr-induced ...

[0018] [6] A positive electrode active material for a lithium ion secondary battery according to any one of [1] to [5], wherein in an X-ray diffraction pattern using a Cu ray source, the peaks of the 108 plane and the 110 plane in the space group R-3m are broken, and the half width of the peak of the 110 plane is greater than 0.10° and less than 0.21°.

[0019] [6] The positive electrode active material for lithium ion secondary battery involved has peaks broken in the 108 plane and the 110 plane, and the half width of the peak in the 110 plane is greater than 0.10° and less than 0.21°. This shows that Ni, Mn and Zr are not phase-separated but uniformly dispersed. That is, it is shown that Ni, Mn and Zr are not phase-separated but solid-dissolved in the lithium transition metal composite oxide. Therefore, it can contribute to further energy efficiency.

[0020] [7] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [6], wherein the lattice constants (a, c, c / a) of the lithium transition metal composite oxide in the space group R-3m are such that the a-axis length is The c-axis length is And c / a is 4.940~4.960.

[0021] [7] The lattice constant of the positive electrode active material for lithium ion secondary batteries involved satisfies a specific numerical range. Therefore, lithium ions are easily diffused in the particles of the lithium transition metal composite oxide, and the resistance is low. Therefore, it can contribute to further energy efficiency.

[0022] [8] A lithium ion secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains the positive electrode active material for a lithium ion secondary battery according to any one of [1] to [7].

[0023] [8] The positive electrode of the lithium ion secondary battery involved contains the above-mentioned positive electrode active material for lithium ion secondary batteries. Therefore, the discharge capacity can be further increased, the number of required batteries can be reduced, and the cost can be reduced. In other words, it can contribute to the efficiency of energy.

[0024] [9] A method for producing a positive electrode active material for a lithium ion secondary battery, which is the method for producing a positive electrode active material for a lithium ion secondary battery according to any one of [1] to [7], the method for producing a positive electrode active material for a lithium ion secondary battery comprising: A process of heat treating a mixture of a lithium compound, a zirconium compound and a nickel-manganese compound at 1025°C to 1150°C for 1 minute to 7 hours or a process of heat treating a mixture of a lithium compound and a nickel-manganese-zirconium ....

[0025] The method including the heat treatment step can produce a positive electrode active material for a lithium ion secondary battery that satisfies the range of the chemical composition of the lithium transition metal composite oxide and the Mn / Ni ratio in the outer layer represented by formula (1).

[0026]

[10] The method for producing a positive electrode active material for a lithium ion secondary battery according to [9], wherein, after the heat treatment step, the step of maintaining the obtained lithium transition metal composite oxide at a temperature of 450° C. to 800° C. for 1 hour to 24 hours is further included.

[0027] By further providing the above-mentioned holding step (slow cooling step), the reduction of the valence of Mn in the lithium transition metal composite oxide can be suppressed to form a more stable structure. Therefore, the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. Therefore, it can contribute to further energy efficiency. Effects of the Invention

[0028] According to the positive electrode active material for lithium ion secondary batteries, the lithium ion secondary batteries, and the method for producing the positive electrode active material for lithium ion secondary batteries of the present invention, the discharge capacity can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The lithium transition metal composite oxides of Examples 1 and 2 are shown in FIG. 6 Graph of Li-MAS-NMR spectrum. Figure 2 The graph shows the powder X-ray diffraction patterns of the lithium transition metal composite oxides of Examples 1 and 2. Figure 3 It is a cross-sectional view schematically showing a lithium ion secondary battery according to one embodiment of the present invention. Figure 4 This is a graph showing the charge and discharge curves of lithium ion secondary batteries using the lithium transition metal composite oxides of Examples 1 and 2. Figure 5 The lithium transition metal composite oxides of Example 3 and Comparative Example 1 are shown in FIG. 6 Graph of Li-MAS-NMR spectrum. Figure 6 The graphs show the powder X-ray diffraction patterns of the lithium transition metal composite oxides of Example 3 and Comparative Example 1. Figure 7 This is a graph showing the charge and discharge curves of lithium ion secondary batteries using the lithium transition metal composite oxides of Example 3 and Comparative Example 1. DETAILED DESCRIPTION

[0030] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0031] [Positive electrode active material for lithium ion secondary batteries] The positive electrode active material for lithium ion secondary batteries of the present embodiment is mainly composed of lithium transition metal composite oxide, and is used for the positive electrode of lithium ion secondary batteries. The lithium transition metal composite oxide "as the main component" means that the content of the lithium transition metal composite oxide is 75% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and may be 100% by mass, relative to the total mass of the positive electrode active material. As long as the function of the present invention is not impaired, the positive electrode active material for lithium ion secondary batteries may also contain components other than the main component.

[0032] The positive electrode active material for lithium ion secondary battery of the present embodiment may contain only one type of lithium transition metal composite oxide, or may contain two or more types of lithium transition metal composite oxide, as long as the main component is the lithium transition metal composite oxide.

[0033] When a positive electrode active material is manufactured with a lithium transition metal composite oxide as the main component, the overall composition ratio (Li:Ni:Mn:Zr) of the lithium transition metal composite oxide is also maintained in the obtained positive electrode active material. When a positive electrode active material obtained with a lithium transition metal composite oxide having such a composition as the main component is used in a secondary battery, a high capacity can be achieved. In addition, the composition ratio of the lithium transition metal composite oxide is adjusted to be the same as the composition ratio required for the desired positive electrode active material.

[0034] (Lithium transition metal composite oxide) The lithium transition metal composite oxide of the present embodiment is a layered rock salt type oxide, and is in the form of particles having an outer layer on the surface.

[0035] In this specification, the average particle size of the particles of the lithium transition metal composite oxide (hereinafter also referred to as "average particle size") is not particularly limited, but is preferably 0.25 to 10 μm, more preferably 0.25 to 5.0 μm, and further preferably 0.50 to 2.5 μm. If the average particle size is above the above lower limit, the productivity of the positive electrode active material for lithium ion secondary batteries can be further improved. If the average particle size is below the above upper limit, the electrochemical characteristics of the lithium ion secondary battery can be made better. The average particle size refers to D50 measured by, for example, a laser diffraction particle size distribution analyzer.

[0036] <Chemical composition> In the past, lithium transition metal composite oxides (such as LiNi 0.5 Mn 0.5 O 2 ), if Li is dissolved in the transition element, Ni 2+ Converted to Ni 3+Therefore, in order to improve the electrochemical properties of the positive electrode active material, it is necessary to increase the amount of Ni used. The present invention is based on the following discovery: 0.5 Mn 0.5 O 2 Add Zr as a constituent element and replace Ni with Li and Zr 0.5 Mn 0.5 , thereby preventing the valence of Ni ions from increasing to 3. Thus, in the present invention, the amount of Ni used can be reduced while maintaining the electrochemical characteristics of the positive electrode active material well.

[0037] The lithium transition metal composite oxide of the present embodiment is represented by the following formula (1). Li m Ni x Mn y Zr z O 2 (1) In the formula (1), m is in the range of 1.0≤m≤1.04, x is in the range of 0.47<x<0.58, y is in the range of 0.40≤y<0.50, and z is in the range of 0<z<0.02.

[0038] The lithium transition metal composite oxide of the present embodiment is more preferably such that m in formula (1) is in the range of 1.02≤m≤1.04, x is in the range of 0.475≤x≤0.55, y is in the range of 0.45≤y≤0.475, and z is in the range of 0.005≤z≤0.015. Specifically, the chemical composition of the lithium transition metal composite oxide used in the present invention is in the range of Li 1.02 Ni 0.55 Mn 0.475 Zr 0.005 O 2 To Li 1.04 Ni 0.475 Mn 0.45 Zr 0.015 O 2 range.

[0039] The chemical composition of the lithium transition metal composite oxide of the present embodiment can be determined by inductively coupled plasma (ICP) emission spectrometry.

[0040] <Surface composition> The particles of the lithium transition metal composite oxide have an outer layer on the surface. In this specification, the "outer layer" refers to the region from the surface of the particle to 25 nm inside the particle. When the particle diameter is less than 50 nm, the particle has a single-layer structure consisting of only the outer layer.

[0041] The content ratio of Mn in the outer layer of the particles of the lithium transition metal composite oxide of the present embodiment is higher than the content ratio of Mn in the composition of the central portion. The ratio of the number of atoms of Mn in the outer layer of the lithium transition metal composite oxide of the present embodiment to the number of atoms of Ni (Mn / Ni ratio) is greater than 1.0 and less than 2.5, preferably greater than 1.0 and less than 2.0, and more preferably greater than 1.0 and less than 1.8. When the Mn / Ni ratio is within the above numerical range, the movement of lithium ions will not be hindered, and the charge and discharge capacity of the lithium ion secondary battery becomes high capacity when used as a positive electrode active material.

[0042] The Mn / Ni ratio can be obtained by quantitative analysis of X-ray photoelectron spectroscopy (XPS). According to XPS, the composition of the manganese-rich surface of the entire particle can be analyzed. That is, the analysis result obtained by XPS does not represent the local composition of the entire surface of one particle, but represents the composition of the entire surface of the particle.

[0043] The ratio of the number of atoms of Ni in the outer layer of the lithium transition metal composite oxide of the present embodiment to the number of atoms of Zr (Ni / Zr ratio) is preferably 6.50 or more and 17.5 or less, more preferably 6.75 or more and 17.5 or less, and further preferably 7.00 or more and 17.5 or less. When the Ni / Zr ratio is within the above numerical range, the surface becomes zirconium (Zr)-rich. Therefore, the increase in the Ni valence and the decrease in the Mn valence can be suppressed, and the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. The Ni / Zr ratio can be determined by quantitative analysis using XPS.

[0044] The ratio of the number of atoms of Mn in the outer layer of the lithium transition metal composite oxide of the present embodiment to the number of atoms of Zr (Mn / Zr ratio) is preferably 13.5 or more and 18.0 or less, more preferably 13.5 or more and 17.5 or less, and further preferably 13.5 or more and 17.0 or less. When the Mn / Zr ratio is within the above numerical range, the surface becomes zirconium (Zr)-rich. Therefore, the increase in the Ni valence and the decrease in the Mn valence can be suppressed, and the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. The Mn / Zr ratio can be determined by quantitative analysis using XPS.

[0045] The particles of the lithium transition metal composite oxide of the present embodiment may be primary particles or secondary particles. In order to obtain relatively dense particles, the particles of the lithium transition metal composite oxide are preferably secondary particles formed by agglomeration of a plurality of primary particles.

[0046] <Lattice constant> The lithium transition metal composite oxide of the present embodiment is a rhombohedral layered compound having a crystal structure of space group R-3m. The lattice constant of the lithium transition metal composite oxide is preferably The c-axis length is and c / a is 4.940 to 4.960. When the lattice constant is within the above range, lithium ions can be easily diffused in the primary particles of the lithium transition metal composite oxide, and the resistance is low. The lattice constant of the crystal can be determined by measuring the X-ray diffraction pattern of the lithium transition metal composite oxide and using each index and the interplanar spacing thereof by the least square method.

[0047] < 6 Li-MAS-NMR spectrum> exist Figure 1 The solid lithium nuclear magnetic resonance ( 6 Li-MAS-NMR) spectrum. The solid line (Example 1) is the spectrum after heat treatment at 1100°C for 5 minutes, and the dotted line (Example 2) is the spectrum after heat treatment at 1100°C for 5 minutes, further kept at 650°C for 19 hours, kept at 550°C for 19 hours, and kept at 450°C for 19 hours. The spectrum confirmed a peak in the range of 500 to 800 ppm. This means that the Li-O layer caused by the Li layer is the main source of Li-MAS-NMR. 6 Ni and Mn in the adjacent transition metal layers are uniformly solid-dissolved, and it is shown that Ni and Mn are uniformly dispersed in the lithium transition metal composite oxide, that is, Li is uniformly solid-dissolved.

[0048] in addition, Figure 1 The spectrum shown does not contain any peaks other than pseudo peaks such as rotating sidebands in the range of 1475 to 1550 ppm. This means that there is no Li 2 MnO 3 The peaks caused by this phenomenon show that there is no LiMn in the transition metal layer. 6 When Ni and Mn are not uniformly dissolved but form Mn-rich domains, the Li 2 MnO 3 The present inventors have confirmed that Figure 1 of 6 In the Li-MAS-NMR spectrum, due to peak separation, no peak other than a pseudo peak exists in the range of 1475 to 1550 ppm. It should be explained that Figure 1 In the figure, “*” refers to the spinning sideband.

[0049] 6The Li-MAS-NMR spectrum can be measured using a solid lithium nuclear magnetic resonance apparatus using a magic angle spinning method.

[0050] Since Ni, Mn, and Zr are uniformly dissolved in the lithium transition metal composite oxide of the present embodiment, when used as a positive electrode active material in a lithium ion secondary battery, the charge and discharge capacity can be increased.

[0051] <X-ray diffraction (XRD) pattern> exist Figure 2 The lithium transition metal composite oxide (Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O 2 ) is an X-ray diffraction (XRD) pattern. Cu (copper) is used as a target for irradiating the electron beam, and Kα rays are used as characteristic X-rays. In the pattern after the raw material mixture was heat treated at 1100°C for 5 minutes (solid line, Example 1), and in the pattern after the raw material mixture was heat treated at 1100°C for 5 minutes, further kept at 650°C for 19 hours, kept at 550°C for 19 hours, and kept at 450°C for 19 hours (dashed line, Example 2), no peak caused by the domain structure was confirmed. In particular, the XRD pattern of the lithium transition metal composite oxide of the present embodiment does not have a peak in the range of 42°≤2θ≤43°. This means that there is no peak caused by Li 2 ZrO 3 The peak caused by γ-ray diffraction ( ΔE) is shown, and it shows that Zr is solid-dissolved in the lithium transition metal composite oxide.

[0052] In addition, Figure 2 In the XRD pattern, the two peaks of the 108 plane and the 110 plane in the space group R-3m are broken and clearly separated. This indicates that Ni, Mn and Zr in the transition metal layer are not phase-separated but uniformly dispersed.

[0053] exist Figure 2 In the figure, the half width of the peak of the 110 face in the space group R-3m is 0.10° or more and 0.21° or less. This shows that Ni, Mn and Zr in the transition metal layer in the lithium transition metal composite oxide are not phase-separated but are solid-dissolved. It should be noted that "the half width is 0.10° or more and 0.21° or less" means that the peak of the 110 face in the space group R-3m is not tailed. The half width of the peak is determined by analyzing the XRD pattern.

[0054] [Method for producing positive electrode active material for lithium ion secondary battery] The positive electrode active material for lithium ion secondary battery of this embodiment contains the above-mentioned lithium transition metal composite oxide as a main component. As a lithium source of the lithium transition metal composite oxide, lithium hydroxide monohydrate (LiOH·H 2 O) and other hydroxides, lithium carbonate (Li 2 CO 3 ) and other carbonates, lithium acetate (CH 3 COOLi), lithium acetate dihydrate (CH 3 COOLi·2H 2 As for the compounds of the nickel source, manganese source and zirconium source of the transition metal, the oxides, hydroxides or metal salts of known nickel, manganese and zirconium can also be widely used without particular limitation. For example, nickel hydroxide (Ni(OH) 2 ), nickel(II) chloride (NiCl 2 ), nickel(II) chloride hexahydrate (NiCl 2 6H 2 O), nickel(II) nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) etc., but are not limited to these. As the manganese compound, manganese (II) chloride (MnCl 2 ), manganese(II) chloride tetrahydrate (MnCl 2 ·4H 2 O), manganese carbonate hexahydrate (MnCO 3 6H 2 O), manganese(II) nitrate hexahydrate (Mn(NO 3 ) 2 6H 2 O) etc., but are not limited to these. As the zirconium compound, zirconium dioxide (ZrO 2 )、Zirconium(IV) sulfate tetrahydrate (Zr(SO 4 ) 2 ·4H 2 O), zirconium (IV) hydroxide (Zr (OH) 4 ), etc., but are not limited to these. The above transition metal compounds can be used alone or as a composite hydroxide (for example, nickel-manganese-zirconium composite hydroxide) by a coprecipitation method or the like.

[0055] The lithium transition metal composite oxide of the present embodiment can be synthesized using a known method. For example, it is possible to prepare a composite hydroxide or composite oxide of a nickel compound and a manganese compound as an intermediate compound, mix the intermediate compound, a zirconium compound and a lithium compound as a raw material mixture, and synthesize the raw material mixture by heat treatment (e.g., calcination) for a given time in a given atmosphere and at a given temperature. In addition, it is also possible to prepare a composite hydroxide or composite oxide of a nickel compound, a manganese compound and a zirconium compound as an intermediate compound, mix the intermediate compound and a lithium compound as a raw material mixture, and synthesize the raw material mixture by heat treatment (e.g., calcination) for a given time in a given atmosphere and at a given temperature.

[0056] The lithium transition metal composite oxide obtained in the above-mentioned heat treatment process is preferably further kept for a given time within a given temperature range by a slow cooling process. The slow cooling conditions vary according to the treatment conditions (heat treatment atmospheres such as oxygen atmosphere, air atmosphere, etc.), and are therefore preferably adjusted appropriately. The inventors have found that by appropriately selecting the above-mentioned heat treatment conditions and the above-mentioned slow cooling conditions, the transition metal of the lithium transition metal composite oxide can be uniformly dispersed, and the Mn / Ni ratio on the particle surface can be increased. Below, the method for manufacturing the positive electrode active material for lithium ion secondary batteries of the present embodiment is further described in detail by way of implementation.

[0057] "First process" In the first step, first, a predetermined amount of a zirconium compound and a predetermined amount of a lithium compound are added to the nickel-manganese compound as an intermediate, and the mixture is dispersed in a solvent such as ethanol and mixed. It should be noted that the predetermined amount of the intermediate compound, the predetermined amount of the zirconium compound, and the predetermined amount of the lithium compound can be mixed not only by wet mixing using a solvent but also by dry mixing without using a solvent. For example, when using zirconium dioxide (ZrO 2 ) as zirconium compound, lithium carbonate (Li 2 CO 3 ) as a lithium compound to synthesize Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O 2 In the case of the above, it is preferred to weigh 1% to 5% more Li than the stoichiometric ratio. 2 CO 3 For example, weigh 2% more Li 2 CO 3 In addition, in the synthesis of Li 1.02 Ni 0.475 Mn 0.475 Zr 0.01 O 2Similarly, in the case of , it is preferred to weigh 1 mass % to 5 mass % more Li than the stoichiometric ratio. 2 CO 3 For example, weigh 2% more Li 2 CO 3 .

[0058] The nickel-manganese compound can be synthesized by a known method. When the nickel-manganese compound is a hydroxide, for example, nickel sulfate hexahydrate (NiSO 4 6H 2 O) and manganese sulfate pentahydrate (MnSO 4 ·5H 2 O) so that the molar ratio of Ni:Mn becomes 1:1, pure water is added thereto to dissolve it, and then an alkaline aqueous solution is added dropwise to the sulfate aqueous solution to coprecipitate it as a nickel-manganese composite hydroxide.

[0059] As an intermediate compound, a nickel manganese zirconium compound may be used instead of the above nickel manganese compound. For example, a given amount of a lithium compound is added to the nickel manganese zirconium compound, and the lithium compound is dispersed in a solvent such as ethanol and mixed. It should be noted that a given amount of the above nickel manganese zirconium compound and a given amount of a lithium compound may be mixed not only by wet mixing using a solvent, but also by dry mixing without using a solvent. For example, when using lithium carbonate (Li 2 CO 3 ) as a lithium compound to synthesize Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O 2 In the case of the above, it is preferred to weigh 1% to 5% more Li than the stoichiometric ratio. 2 CO 3 For example, weigh 2% more Li 2 CO 3 In addition, in the synthesis of Li 1.02 Ni 0.475 Mn 0.475 Zr 0.01 O 2 Similarly, in the case of , it is preferred to weigh 1 mass % to 5 mass % more Li than the stoichiometric ratio. 2 CO 3 For example, weigh 2% more Li 2 CO 3 .

[0060] The nickel manganese zirconium compound can be synthesized using a known method. When the nickel manganese zirconium compound is a hydroxide, for example, nickel sulfate hexahydrate (NiSO 4 6H 2O), manganese sulfate pentahydrate (MnSO 4 ·5H 2 O) and zirconium (IV) sulfate tetrahydrate (Zr(SO 4 ) 2 ·4H 2 O) so that the molar ratio of Ni:Mn:Zr is 1:1:x (x is preferably 0.005 to 0.04), pure water is added thereto to dissolve it, and then an alkaline aqueous solution is added dropwise to the sulfate aqueous solution to coprecipitate it as a nickel-manganese-zirconium composite hydroxide.

[0061] As a precursor, a mixture of a lithium compound, a zirconium compound and a nickel-manganese compound is crushed into a preferred size and mixed, or a mixture of a lithium compound and a nickel-manganese-zirconium compound is crushed into a preferred size and mixed, and then filled into a crucible to heat-treat the mixture. As a crucible, an alumina crucible, an alumina crucible, a platinum crucible, a gold crucible, etc. are used. The heat treatment of the mixture, for example, uses a firing furnace or a roller kiln.

[0062] The above mixture loaded into the sagger and the crucible is heated at a heating rate of 5°C / min to 25°C / min, preferably 10°C / min to 25°C / min to reach the heat treatment temperature. The heat treatment atmosphere is not particularly limited, and examples include the atmosphere (under air atmosphere), oxygen flow, etc. The heat treatment atmosphere is preferably an oxygen flow. The heat treatment time can be appropriately set according to the heat treatment temperature. It should be noted that the heat treatment time refers to the time for maintaining the heat treatment temperature.

[0063] In the case of lithium compounds (e.g., Li 2 CO 3 ), zirconium compounds (e.g., ZrO 2 ) and a nickel-manganese compound, the heat treatment temperature is preferably 1025° C. to 1150° C., more preferably 1050° C. to 1125° C. The heat treatment time is preferably 1 minute to 7 hours, more preferably 2 minutes to 6 hours, further preferably 3 minutes to 5 hours, particularly preferably 5 minutes to 3 hours.

[0064] In addition, in the case of lithium compounds (such as Li 2 CO 3 ) and a mixture of nickel-manganese-zirconium compounds are subjected to heat treatment, the heat treatment temperature is preferably 1025° C. to 1150° C., more preferably 1050° C. to 1125° C. The heat treatment time is preferably 1 minute to 7 hours, more preferably 2 minutes to 6 hours, further preferably 3 minutes to 5 hours, particularly preferably 5 minutes to 3 hours.

[0065] "Second process" In the second step, the powder obtained after the heat treatment in the first step is cooled to 800° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then the powder is maintained at 800° C. for 0.5 hours to 12 hours. The atmosphere when the powder is maintained at 800° C. is not particularly limited, and examples thereof include air (under air atmosphere), air flow, oxygen flow, and the like.

[0066] The method for manufacturing a positive electrode active material for a lithium ion secondary battery of the present embodiment may have a step of maintaining the powder at 750°C for more than 0.5 hours and less than 12 hours after the second step. In this case, after the powder maintained at 800°C in the second step is cooled at a cooling rate of 10°C / min to reach 750°C, the powder is maintained at 750°C for more than 0.5 hours and less than 12 hours. The atmosphere when the powder is maintained at 750°C is not particularly limited, and examples include the atmosphere (under air atmosphere), air flow, oxygen flow, etc.

[0067] "Third Process" In the third step, the powder maintained at 750° C. in the second step is cooled to 700° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then maintained at 700° C. for 0.5 hour to 12 hours. The atmosphere when the powder is maintained at 700° C. is not particularly limited, and examples thereof include air (air atmosphere), air flow, oxygen flow, and the like.

[0068] "Fourth Process" In the fourth step, the powder maintained at 700° C. in the third step is cooled to 650° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then maintained at 650° C. for 0.5 hours to 12 hours. The atmosphere when the powder is maintained at 650° C. is not particularly limited, and examples thereof include air (air atmosphere), air flow, oxygen flow, and the like.

[0069] The Fifth Process In the fifth step, the powder maintained at 650° C. in the fourth step is cooled to 600° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then maintained at 600° C. for 0.5 hour to 20 hours. The atmosphere when the powder is maintained at 600° C. is not particularly limited, and examples thereof include air (under air atmosphere), air flow, oxygen flow, and the like.

[0070] "Sixth Process" In the sixth step, the powder maintained at 600°C in the fifth step is cooled at a temperature reduction rate of 10°C / min to 400°C to 500°C, and then the powder is maintained at 400°C to 500°C for 0.5 hours to 30 hours. The sixth step may be a step of maintaining the powder at 450°C for 0.5 hours to 30 hours, and then maintaining the powder at 400°C for 0.5 hours to 30 hours. In addition, the sixth step may be a step of maintaining the powder at 500°C for 0.5 hours to 20 hours.

[0071] The slow cooling process of the second step to the sixth step can be appropriately changed or omitted as needed. In one embodiment, the slow cooling process is preferably maintained at 450°C or above and 800°C or below for more than 1 hour and less than 24 hours after heat treatment, more preferably for more than 2 hours and less than 20 hours, and most preferably for 19 hours. In addition, the slow cooling process can be performed more than 2 times as long as the maintained temperature is lowered in stages. The positive electrode active material for lithium ion secondary batteries of this embodiment can further improve the Mn / Ni ratio on the particle surface of the lithium transition metal composite oxide by appropriately selecting the slow cooling conditions.

[0072] [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode contains a positive electrode active material having the above-mentioned lithium transition metal composite oxide as a main component. The lithium ion secondary battery of this embodiment may include other battery elements as necessary.

[0073] The lithium ion secondary battery of this embodiment can directly adopt the battery elements of known lithium ion secondary batteries except that the positive electrode contains the positive electrode active material with the above-mentioned lithium transition metal composite oxide as the main component. The lithium ion secondary battery of this embodiment can be any structure of coin type, button type, cylindrical type, square type, and laminated type. In addition, the lithium ion secondary battery of this embodiment can be applied to a wide range of uses such as mobile devices such as mobile phones and notebook computers, and vehicle-mounted use.

[0074] Hereinafter, the lithium ion secondary battery of the present embodiment will be described as a lithium ion secondary battery (coin-type lithium ion secondary battery) using an electrolyte solution. Each battery element described below can also be similarly applied to an all-solid-state lithium ion secondary battery that does not use an electrolyte solution.

[0075] Figure 3 Schematically shows a cross-sectional view of a lithium-ion secondary battery according to this embodiment. Figure 3 In FIG. 1 , an example in which the lithium ion secondary battery of this embodiment is a coin-type lithium ion secondary battery is shown. Figure 3As shown, the lithium ion secondary battery 1 of the present embodiment includes a negative electrode can (negative electrode terminal) 20 , a negative electrode 3 , a separator 4 impregnated with an electrolyte, an insulating spacer (gasket) 5 , a positive electrode 2 , and a positive electrode can 10 .

[0076] The positive electrode can 10 is arranged on the lower side of the separator 4, and the negative electrode can 20 is arranged on the upper side of the separator 4, and the positive electrode can 10 and the negative electrode can 20 form the outer shape of the lithium ion secondary battery 1. Between the positive electrode can 10 and the negative electrode can 20, the positive electrode 2 and the negative electrode 3 are arranged via the separator 4 impregnated with the electrolyte, and the positive electrode 2 and the negative electrode 3 are separated by the separator 4. The positive electrode can 10 and the negative electrode can 20 are electrically insulated by the insulating gasket 5.

[0077] The lithium ion secondary battery 1 can be manufactured by mixing a conductive agent, a binder, etc. with the positive electrode active material for a lithium ion secondary battery of this embodiment as necessary to prepare a positive electrode composite, and press-bonding the composite to a current collector (not shown) to produce the positive electrode 2 . As the current collector, a stainless steel mesh, aluminum foil, etc. can be preferably used. As the conductive agent, acetylene black, Ketjen black, etc. can be preferably used. As the binder, tetrafluoroethylene, polyvinylidene fluoride, etc. can be preferably used.

[0078] The combination of the positive electrode active material, the conductive agent and the binder in the positive electrode composite is not particularly limited. The content of the conductive agent in the positive electrode composite is preferably 1% to 15% by mass, and more preferably 0.1% to 5% by mass. The content of the binder in the positive electrode composite is preferably 0.1% to 10% by mass, and more preferably 0.1% to 5% by mass. The remainder of the positive electrode composite (the portion other than the positive electrode active material and the conductive agent) is preferably combined with the positive electrode active material, the conductive agent and the binder to form the positive electrode active material.

[0079] In the lithium-ion secondary battery 1, as the negative electrode 3 relative to the positive electrode 2, for example, a known negative electrode can be used, which uses metal materials such as metallic lithium and lithium alloys, carbon materials such as graphite and MCMB (mesocarbon microbeads), silicon (Si), Si alloys, silicon oxide and other silicon materials as negative electrode active materials to function and can absorb and release lithium.

[0080] The separator 4 and the battery container (positive electrode can 10 and negative electrode can 20 ) can adopt known battery elements.

[0081] As the electrolyte, a known electrolyte solution, solid electrolyte, etc. can be used. As the electrolyte solution, for example, an electrolyte solution obtained by dissolving electrolytes such as lithium perchlorate and lithium hexafluorophosphate in solvents such as ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), and diethyl carbonate (DEC) can be used.

[0082] The all-solid lithium ion secondary battery can have the same structure as a known all-solid lithium ion secondary battery except that a positive electrode active material containing the above-mentioned lithium transition metal composite oxide as a main component is used.

[0083] In the case of an all-solid-state lithium-ion secondary battery, as the electrolyte, for example, a polymer solid electrolyte such as a polyethylene oxide-based polymer compound, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain, a sulfide solid electrolyte, an oxide solid electrolyte, or the like can be used.

[0084] The positive electrode of the all-solid lithium ion secondary battery may include, for example, a positive electrode composite material containing a solid electrolyte in addition to the above-mentioned positive electrode active material, conductive agent, and binder, and may be supported on a positive electrode collector such as aluminum, nickel, or stainless steel.

[0085] The lithium ion secondary battery 1 of the present embodiment can have a high capacity because the positive electrode 2 contains a positive electrode active material having the above-mentioned lithium transition metal composite oxide as a main component. Example

[0086] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.

[0087] [Example 1] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O 2 ) Weighing Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 , and Zr(OH) 4 (manufactured by Sigma-Aldrich) were weighed based on a stoichiometric ratio so that the molar ratio of Li:Ni:Mn:Zr was 1.04:0.475:0.475:0.01, and Li was weighed based on a stoichiometric ratio in consideration of Li evaporation. 2 CO 3 Increase by 3% by mass to make Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 and Zr(OH) 4The total mass of (Sigma-Aldrich) is 2.1g. They are dispersed in ethanol and mixed using a mortar. Then, they are filled into a platinum crucible of JIS standard. Using a sintering furnace, the mixture filled in the platinum crucible is heated at a heating rate of 15°C / min in air, sintered at 1100°C for 5 minutes, and then left until the temperature of the obtained powder becomes room temperature (25°C), thereby obtaining the lithium nickel manganese zirconium oxide of Example 1.

[0088] [Example 2] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O 2 ) Weighing Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 , and Zr(OH) 4 (manufactured by Sigma-Aldrich) was weighed based on a stoichiometric ratio so that the molar ratio of Li:Ni:Mn:Zr was 1.04:0.475:0.475:0.01, and Li was weighed based on a stoichiometric ratio in consideration of Li evaporation. 2 CO 3 Increase by 3% by mass to make Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 and Zr(OH) 4 The total mass of the lithium nickel manganese zirconium oxide (Sigma-Aldrich) was 2.1 g. They were dispersed in ethanol and mixed using a mortar. Then, they were filled into a platinum crucible of JIS standard. Using a sintering furnace, the mixture filled in the platinum crucible was heated at a heating rate of 15°C / min in air and sintered at 1100°C for 5 minutes to obtain a powder of lithium nickel manganese zirconium oxide. After the heat-treated powder is cooled at a cooling rate of 10°C / min to 650°C, the powder is kept in air at 650°C for 19 hours. Next, after cooling at a cooling rate of 10°C / min to 550°C, the cooled powder is kept in air at 550°C for 19 hours. Furthermore, after cooling at a cooling rate of 10°C / min to 450°C, the cooled powder is kept in air at 450°C for 19 hours. Then, the powder is left to stand until the temperature of the powder reaches room temperature (25°C), and the lithium nickel manganese zirconium oxide of Example 2 is obtained.

[0089] [Example 3] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.02 Ni 0.57 Mn 0.40 Zr 0.01 O 2 ) Weighing Li 2 CO 3 (High-purity chemical), Ni(OH) 2 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 , and Zr(OH) 4 (manufactured by Sigma-Aldrich) was weighed based on a stoichiometric ratio so that the molar ratio of Li:Ni:Mn:Zr was 1.02:0.57:0.40:0.01, and Li was weighed based on a stoichiometric ratio in consideration of Li evaporation. 2 CO 3 Increase by 2 mass% to make Li 2 CO 3 (High-purity chemical), Ni(OH) 2 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 , and Zr(OH) 4 The total mass of (Sigma-Aldrich) is 2.1g. They are dispersed in ethanol and mixed in a mortar. Then, they are filled into a platinum crucible of JIS standard. Using a sintering furnace, the mixture filled in the platinum crucible is heated at a heating rate of 15°C / min in air, sintered at 1050°C for 30 minutes, and then placed until the temperature of the obtained powder becomes room temperature (25°C), to obtain the lithium nickel manganese zirconium oxide of Example 3.

[0090] [Comparative Example 1] (Synthesis of lithium nickel manganese oxide: Li 1.04 Ni 0.48 Mn 0.48 O 2 ) Weighing Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 (NARD) was weighed so that the molar ratio was Li:Ni:Mn=1.04:0.48:0.48, and Li was weighed based on the stoichiometric ratio in consideration of Li evaporation. 2 CO3 Increase by 2 mass% to make Li 2 CO 3 (High-purity chemical), Ni 0.5 Mn 0.5 (OH) 2 The total mass of (NARD) is 2.1g. They are dispersed in ethanol and mixed in a mortar. Then, they are filled in a platinum crucible of JIS standard. Using a sintering furnace, the mixture filled in the platinum crucible is heated at a heating rate of 15°C / min in air, sintered at 950°C for 30 minutes, and then placed until the temperature of the obtained powder becomes room temperature (25°C), to obtain the lithium nickel manganese oxide of Comparative Example 1.

[0091] (analyze) The chemical composition of the sample obtained in Example 1 was analyzed by an ICP emission spectrometer (trade name: Agilent 5110VDV, manufactured by Agilent Technologies), and the results are shown in Table 1. As shown in Table 1, it was confirmed that Li:Ni:Mn:Zr=1.04:0.475:0.475:0.01. In addition, the X-ray diffraction (XRD) pattern of the obtained sample was measured by a powder X-ray diffraction device (trade name: SmartLab, manufactured by Rigaku). Cu (copper) was used as the target for irradiating the electron beam, and Kα rays were used as the characteristic X-rays. The lattice constant was calculated by the least square method using the indices and interplanar spacing of the obtained XRD pattern. The space group of the obtained sample was set to R-3m and the lattice constant was calculated. The result was a = 2.88560 (4) c=14.2857(3) c / a = 4.9502. The half width of the peak of the 110 plane in the space group R-3m is 0.1079 (17)°. The powder X-ray diffraction pattern is shown in Figure 2 Table 1 shows the lattice constants and the half widths of the peaks. In addition, the X-ray photoelectron spectroscopy (XPS) analysis device (trade name: K-Alpha + The composition of the surface layer of the obtained sample was analyzed by quantitative analysis of XPS (manufactured by Thermo Fisher Scientific), and the results are shown in Table 1. As shown in Table 1, the Mn / Ni ratio in the surface layer was 1.0. It should be noted that the measurement conditions of the XPS measurement are as follows. 《XPS measurement conditions》 Model used: Made by Thermo Fisher Scientific, K-Alpha + (Product Name) X-ray irradiation: Single crystal spectrometry AlKα (12keV, 72W) X-ray spot diameter: 400 μm Neutralizing electron gun: Use Reference spectrum: CC, CH 284.6eV Detection depth: 6~7nm

[0092] Furthermore, the samples of Example 1 and Example 2 obtained were analyzed by Li-MAS-NMR (trade name: AVANCE 300, manufactured by Bruker). The results are shown in Figure 1 .according to Figure 1 The results shown confirm that 6 In the Li-MAS-NMR spectrum, the samples of Example 1 and Example 2 have peaks in the range of 500 to 800 ppm. In addition, it was confirmed that the samples of Examples 1 and 2 had no peak other than the spinning sideband in the range of 1475 to 1550 ppm.

[0093] The samples obtained in Examples 2 to 3 and Comparative Example 1 were also subjected to ICP emission spectrometry, powder X-ray diffraction measurement, XPS analysis, and 6 Li-MAS-NMR measurement. The results are shown in Table 1. Figure 2 , Figure 5 ,as well as Figure 6 In Table 1, “half width of peak (°)” indicates the half width of the peak of the 110 plane in the space group R-3m.

[0094] [Table 1]

[0095] according to Figure 2 The XRD patterns shown can confirm that the samples of Example 1 and Example 2 have no peak in the range of 42°≤2θ≤43°. In addition, it can be confirmed that the peaks of the 108 plane and the 110 plane in the space group R-3m of the samples of Example 1 and Example 2 are broken. Furthermore, as shown in Table 1, the half width of the peak of the 110 plane in the space group R-3m of the samples of Example 1 and Example 2 is greater than 0.10° and less than 0.21°.

[0096] like Figure 5 As shown, it can be confirmed that 6 In the Li-MAS-NMR spectrum, the sample of Example 3 has a peak in the range of 500 to 800 ppm. In addition, it can be confirmed that the sample of Example 3 has no peak other than the spinning sideband in the range of 1475 to 1550 ppm. In contrast, the sample of Comparative Example 1, which does not contain zirconium in the chemical composition and has an outer layer Mn / Ni ratio of less than 1.0, 6 In the Li-MAS-NMR spectrum, although there is a peak in the range of 500 to 800 ppm, a peak is confirmed in the range of 1475 to 1550 ppm.

[0097] like Figure 6 As shown in Table 1, it can be confirmed that the sample of Example 3 has no peak in the range of 42°≤2θ≤43°. In addition, it can be confirmed that the peaks of the 108 plane and the 110 plane in the space group R-3m of the sample of Example 3 are broken. Furthermore, as shown in Table 1, the half width of the peak of the 110 plane in the space group R-3m of the sample of Example 3 is greater than 0.10° and less than 0.21°. In contrast, the sample of Comparative Example 1 which does not contain zirconium in the chemical composition and has an outer layer Mn / Ni ratio of less than 1.0 has no peak in the range of 42°≤2θ≤43°, but no peak breakup of the 108 plane and 110 plane in the space group R-3m is confirmed.

[0098] [Manufacturing of lithium-ion secondary batteries] The lithium nickel manganese zirconium oxides of Examples 1 to 3 and the lithium nickel manganese oxide of Comparative Example 1 were used as positive electrode active materials, respectively, and acetylene black (AB) as a conductive agent and polyvinylidene fluoride (PVDF) as a binder were mixed in a weight ratio of 8:1:1 using NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a paste. Then, it was applied to an aluminum foil with a thickness of 15 μm and dried to prepare a 14φ positive electrode. The coating area density was 4.5 mg / cm 2 , volume density is 2.3g / cm 3 For the positive electrode, lithium metal with a thickness of 200 μm and a diameter of 16 was used as the counter electrode, and a polyethylene microporous membrane with a thickness of 20 μm and a diameter of 18 was used as the separator. The electrolyte was lithium hexafluorophosphate (LiPF 6 ) was dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio 3:4:3) to obtain a 1.2 mol / L solution to prepare Figure 3 A lithium ion secondary battery (2032 coin-type battery) having the structure shown is manufactured according to a known battery construction and assembly method.

[0099] [Charge and discharge test] For each of the prepared lithium ion secondary batteries, a charge and discharge test was performed at a temperature of 25°C, at a rate of 0.05C (1C: 250 mA / g), at a current density of 12.5 mA / g, and at a cutoff potential of 4.7V to 2.5V or 4.8V to 2.5V, to evaluate the initial discharge capacity. The charge and discharge test started with charging.

[0100] exist Figure 4 In the figure, the charge and discharge curves in Example 1 and Example 2 are shown. Figure 4 , the voltage change during discharge, in which the battery voltage becomes lower as the capacity increases, and the voltage change during charge, in which the battery voltage becomes higher as the capacity increases, are shown.

[0101] like Figure 4 As shown, it can be seen that the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 2 as the positive electrode active material has a higher capacity than the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 1 as the positive electrode active material. It is speculated that this is because, in Example 2, by implementing a staged slow cooling process, the structure of the lithium nickel manganese zirconium oxide becomes more stable, the dissolution of Ni into the electrolyte can be suppressed, and the Mn / Ni ratio of the outer layer of the particles of the lithium nickel manganese zirconium oxide can be further increased. In Example 1, if the heat treatment conditions are appropriately performed, it can also be expected to become a higher capacity.

[0102] exist Figure 7 In the figure, the charge and discharge curves in Example 3 and Comparative Example 1 are shown. Figure 7 , the voltage change during discharge, in which the battery voltage becomes lower as the capacity increases, and the voltage change during charge, in which the battery voltage becomes higher as the capacity increases, are shown.

[0103] like Figure 7 As shown, it can be seen that the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 3 as the positive electrode active material has a higher capacity than the lithium ion secondary battery using the lithium nickel manganese oxide of Comparative Example 1 as the positive electrode active material.

[0104] [Cycle test] For each lithium ion secondary battery produced, after the initial discharge capacity evaluation, 100 cycle tests were performed at a temperature of 25°C, with a current density of 12.5 mA / g and a cutoff potential of 4.3 V to 2.5 V, and the capacity retention rate (discharge capacity of the 100th cycle / discharge capacity of the 1st cycle) was evaluated. The charge and discharge test started with charging. The results are shown in Table 1. The higher the capacity retention rate, the better the cycle characteristics.

[0105] As shown in Table 1, the lithium ion secondary batteries of Examples 1 to 3 to which the present invention is applied exhibited a high capacity retention rate of 95% or more. On the other hand, the capacity retention rate of the lithium ion secondary battery of Comparative Example 1, in which zirconium was not contained in the chemical composition and the Mn / Ni ratio of the outer layer was less than 1.0, was 88%.

[0106] From the above results, it is clear that according to the present invention, a positive electrode active material for a lithium ion secondary battery capable of further improving the discharge capacity and a lithium ion secondary battery including the positive electrode active material can be provided. Explanation of symbols

[0107] 1: Lithium-ion secondary battery 2: Positive electrode 3: Negative electrode 4: Isolation parts 5: Insulation pad (gasket) 10: Positive electrode tank 20: Negative tank (negative terminal).

Claims

1. A positive electrode active material for a lithium ion secondary battery, comprising a lithium transition metal composite oxide as a main component, wherein: The lithium transition metal composite oxide is in the form of particles having an outer layer on the surface. The lithium transition metal composite oxide is represented by the following formula 1: Formula 1: Li m Nor x Mn y Zr z O2 In Formula 1, m is in the range of 1.0≤m≤1.04, x is in the range of 0.47<x<0.58, y is in the range of 0.40≤y<0.50, and z is in the range of 0<z<0.02, The ratio of the number of Mn atoms to the number of Ni atoms in the outer layer, that is, Mn / Ni ratio, is 1.0 or more and 2.5 or less.

2. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein The ratio of the number of Ni atoms to the number of Zr atoms in the outer layer, that is, Ni / Zr ratio, is 6.50 or more and 17.5 or less.

3. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein In solid lithium NMR analysis using magic angle spinning 6 The spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR has a peak in the range of 500 to 800 ppm.

4. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein In solid lithium NMR analysis using magic angle spinning 6 In the spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR, there is no peak in the range of 1475 to 1550 ppm.

5. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein In the X-ray diffraction pattern using a Cu ray source, there is no peak in the range of 42°≤2θ≤43°.

6. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein In the X-ray diffraction pattern using a Cu ray source, the peaks of the 108 plane and the 110 plane in the space group R-3m are broken, and the half width of the peak of the 110 plane is 0.10° or more and 0.21° or less.

7. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein Regarding the lattice constants (a, c, c / a) of the lithium transition metal composite oxide in the space group R-3m, the a-axis length is The c-axis length is And c / a is 4.940~4.

960.

8. A lithium ion secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The positive electrode contains the positive electrode active material for a lithium ion secondary battery according to any one of claims 1 to 7.

9. A method for producing a positive electrode active material for a lithium ion secondary battery, which is the method for producing a positive electrode active material for a lithium ion secondary battery according to any one of claims 1 to 7, wherein: The method for producing the positive electrode active material for a lithium ion secondary battery comprises: A process of heat treating a mixture of a lithium compound, a zirconium compound and a nickel manganese compound at 1025° C. to 1150° C. for 1 minute to 7 hours, or heat treating a mixture of a lithium compound and a nickel manganese zirconium compound at 1025° C. to 1150° C. for 1 minute to 7 hours.

10. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 9, wherein: After the heat treatment step, the method further includes maintaining the obtained lithium transition metal composite oxide at 450° C. to 800° C. for 1 hour to 24 hours.

Citation Information

Patent Citations

  • Precursor, method for manufacturing precursor, positive electrode material, method for manufacturing positive electrode material, and lithium-ion secondary cell

    WO2020209239A1